The Linkage Between Burnout, Quality of Work Life, and Job Performance Among Fintech Company Employee Management: The Role of Job Satisfaction - Mario Chrissendy Dian Saputra; Aryana Satrya (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
The intense competition among Fintech companies requires management to maintain job performance. Job performance can be achieved through employee job satisfaction. Quality of work life can support the achievement of performance and employee performance, but burnout can reduce the performance of company employees. This study examines the effects of burnout, quality of work life, job satisfaction, indirect effects of burnout, and quality of work life on job performance through job satisfaction. This research was conducted at Fintech companies in Indonesia using a quantitative research design. Data were collected through questionnaires employing the Likert scale, which was further analyzed using SEM-PLS. The results showed that burnout has a negative and significant effect on job performance, while quality work of life has a positive and significant effect on job performance. In addition, job satisfaction has a significant effect on job performance. The indirect effects of burnout on job performance through job satisfaction are significant, as well as quality work of life and job performance. Keywords: Burnout, Quality of work life, Job satisfaction, Job performance